The Relationship between Medication Adherence, Self-Efficacy, and Quality of Life in Patients with Acute Myocardial Infarction - Melinar Fitra Zahrani Moha; Chamim Faizin; Nina Anggraeni Noviasari (Newinera Publisher, 2026)
AMI is one of the most serious cardiovascular diseases, associated with impaired quality of life, increased morbidity and mortality, making it the number one cause of death in the world. The use of medications for secondary prevention is a cornerstone in the treatment of coronary artery disease. Self-efficacy is an important predictor of adherence to treatment. Therefore, high self-efficacy is associated with health which can improve the patient’s quality of life. The aim of this study was to analyze the relationship between medication adherence and self-efficacy with the quality of life of patients who had been diagnosed with acute myocardial infarction at Muhammadiyah Hospital Semarang. The type of quantitative research was analytical observational with a cross-sectional approach. Research respondents were patients who had been diagnosed with AMI from June 2022-June 2023 who were taken through total sampling taking through the sample criteria. Inclusion was 47 and exclusion was 27 respondents. Data analysis uses the chi-square test, significant if p<0.05. 34 respondents were compliant in taking medication (72.3%), 13 respondents were not compliant in taking medication (27.7%). 28 respondents had high self-efficacy (59.6%), 19 respondents had low self-efficacy (40.4%). 38 respondents had a good quality of life (80.9%) and 9 respondents had a poor quality of life (19.1%). As a result, there is no relationship between medication adherence with the quality of life of acute myocardial infarction patients. There is a relationship between self-efficacy with the quality of life of acute myocardial infarction patients.